2002
DOI: 10.1097/00024382-200207000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Epinephrine as a Mediator of Pulmonary Neutrophil Sequestration

Abstract: Neutrophil-mediated lung injury is a potential complication of trauma and sepsis. Concomitant with trauma and sepsis, there is an immediate and sustained systemic elevation of catecholamines including epinephrine. In the absence of trauma or sepsis, we examined whether epinephrine contributes to the accumulation of neutrophils in the lung. Eight- to 12-week-old male CF-1 mice were injected i.p. with 0.2 mL of normal saline or epinephrine (0.1-5.0 mg/kg). An unmanipulated control group was included to examine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Zang et al [55] have shown that oxygen radicals play an important role in the nonvagal component of the noncholinergic bronchoconstriction in guinea pigs in vivo . Morken et al [56] have shown that there is an immediate and sustained systemic elevation of catecholamines including epinephrine, which may set the stage for development of neutrophils-mediated acute lung injury. Furthermore, it has been reported that stress and hypoxia of anaphylaxis cause catecholamine release, loss of choline-containing phospholipids, and thereby ARDS [57].…”
Section: Discussionmentioning
confidence: 99%
“…Zang et al [55] have shown that oxygen radicals play an important role in the nonvagal component of the noncholinergic bronchoconstriction in guinea pigs in vivo . Morken et al [56] have shown that there is an immediate and sustained systemic elevation of catecholamines including epinephrine, which may set the stage for development of neutrophils-mediated acute lung injury. Furthermore, it has been reported that stress and hypoxia of anaphylaxis cause catecholamine release, loss of choline-containing phospholipids, and thereby ARDS [57].…”
Section: Discussionmentioning
confidence: 99%
“…An additional important benefit of vasopressin therapy, observed by us and others (9,11), was its ability to decrease the need for catecholamine agonists, especially the epinephrine dose. This results in a potential reduction in adverse effects of epinephrine on the cardiovascular system such as severe arrhythmia and increased myocardial oxygen consumption, resulting in a severe mismatch of cardiac oxygen delivery (1,(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…These elevated levels of epinephrine can result in enhanced release of pro-inflammatory cytokines including tumor necrosis factor-α (TNFα), interleukin (IL)-1ÎČ, and IL-6 (Frost et al , 2004; Johnson et al , 2005; Wong et al , 2012). Since these cytokines can recruit PMNs to the site of inflammation, their generation as a result of catecholamine stress could provide a link to the observed increase in PMN trafficking to the lung and liver of mice that have been challenged with high doses of epinephrine (Morken et al , 2002; von Montfort et al , 2008). Additionally, extraneuronal generation of epinephrine within the wound by PMNs themselves provides a potential for amplification of the catecholamine-mediated inflammatory response (Flierl et al , 2007).…”
Section: Introductionmentioning
confidence: 99%